2022
DOI: 10.1002/jgh3.12836
|View full text |Cite
|
Sign up to set email alerts
|

Depression is associated with increased disease activity in patients with ulcerative colitis: A propensity score‐matched analysis using a nationwide database in Japan

Abstract: Background and Aim The incidence and prevalence of psychiatric disorders are elevated in patients with inflammatory bowel disease (IBD). Whether psychiatric disorders could affect the clinical course of IBD is uncertain and controversial. We aimed to evaluate the impact of psychiatric disorders, particularly depression, on the clinical course of IBD using a nationwide database in Japan. Methods We collected data on admissions with IBD using the Diagnosis Procedure Combination database system introduced in Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…10 A systematic review showed that in young IBD patients the presence of psychological morbidity decreased treatment adherence by 12%. 30 Anxiety, depression, stress, stigmatization leading to isolation, [31][32][33] are all problems investigated in UC patients. Addressing mental health problems in patients with IBD can improve their adherence to treatment and the somatic disease course and, consequently, reduce morbidity.…”
Section: Discussion Adherencementioning
confidence: 99%
“…10 A systematic review showed that in young IBD patients the presence of psychological morbidity decreased treatment adherence by 12%. 30 Anxiety, depression, stress, stigmatization leading to isolation, [31][32][33] are all problems investigated in UC patients. Addressing mental health problems in patients with IBD can improve their adherence to treatment and the somatic disease course and, consequently, reduce morbidity.…”
Section: Discussion Adherencementioning
confidence: 99%
“…Previously, we conducted clinical research on lower gastrointestinal diseases using big data analytics on a national scale [8][9][10][11][12][13][14][15]. We herein contracted DeSC Healthcare, Inc. to use their dataset of national claim database.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, a nationwide database, the so‐called big data, provides an adequate number of samples and enables the analysis of rare diseases and situations, such as those previously reported. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 Therefore, this study aimed to clarify the clinical practice of EOUC and compare the differences in clinical course between EOUC and NEOUC using a nationwide claims database in Japan.…”
Section: Introductionmentioning
confidence: 99%